CREATION OF COLLABORATIVE DEVELOPMENT ENVIRONMENT IN THE SYSTEM OF DISTANCE LEARNING - Malieieva, Julia; Kosenko, Viktor; Malyeyeva, Olga; Svetlichnyj, Dmitrij (Sučasnij stan naukovih doslìdženʹ ta tehnologìj v promislovostì (Online), 2019)
The subject of the study in the article is methods and tools for the creation and implementation of distance learning systems (DLS). The interactive capabilities used in the distance education system, programs and information delivery systems allow for feedback, dialogue and ongoing support that are not possible in most traditional learning systems. The purpose of the article is to create a collaborative environment for developing software products in the system of distance learning by forming an interactive platform with the help of Sphere Engine, which provides the ability to debug the code in many programming languages.  At the same time, the following tasks are solved: a review and comparison of existing systems of distance learning; analysis of the functional and features of the Sphere Engine platform; development of the integration algorithm of the service with the system Moodle. Methods: methods of information processing, methods and information technologies for the creation of electronic distance learning courses. Results. As a result of the review and comparison of existing distance learning systems and software verification tools, the tools that best meet the needs for collaborative development environments, namely the Moodle DLS and the Sphere Engine service, are selected. The analysis of the functional and features of the Sphere Engine platform is carried out: a diagram of the work of the api compilers of the service is shown, which illustrates the process of execution of the program from the moment of its sending to the results of execution; The concept of a pool script in graphical form is provided.  A prototype collaborative development environment created in the form of a web application is created, the prototype architecture is described. An algorithm for integration of the Sphere Engine service with the Moodle system is developed.  In detail, the stages of the integration algorithm are considered on the example of testing the work environment of the development of the course "Web-technologies and web-design". Conclusions. An interactive module is created with the help of Sphere Engine, which allows you to perform laboratory work on programming disciplines and to carry out full control over their execution. Thus, the degree of automation of the educational process in institutions of higher education increases.